CULTURE AND EVOLUTION OF BAKPIA PATHOK TASTE AS A GASTRONOMIC TOURIST ATTRACTION IN YOGYAKARTA - Ustradi Osijo, Immanuel; Sudarmiatin; Tri Djatmika RWW, Ery (Nusantara Economics and Entrepreneurships Journals, 2023)
The purpose of this study is to find out the culture, history, and evolution of the taste of "Bakpia Pathok 25" and analyze its gastronomic tourism potential as a culinary tourism object in Malioboro, Yogyakarta. This research applies qualitative methods. The study population in this study was limited to Bakpia Pathok 25 which is only located in Kampung Pathuk because of its famous reputation in Yogyakarta. The sampling techniques used for this study were interviews, observation and documentation. SWOT analysis is used as data analysis to get an overview of internal and external factors that affect Bakpia Pathok 25 as a potential for gastronomic tourism and culinary tourism attraction. The results showed that the history of Bakpia Pathok 25 is a typical Chinese food called "Tou Luk Pia" which is then interpreted as mung bean pia cake. The Chinese then brought this food to Indonesia in the 1948s. Culture "Bakpia Pathok 25 Bakpia is a form of food acculturation in the culinary field that occurs between Indonesian and Chinese people and by producing bakpia, the bakpia merti procession is held as a form of gratitude of the Pathuk people for abundant sustenance